(untitled) (Bangladesh Journal of Psychiatry, 2021)
Human civilizations affected by internet in an all-encompassing manner. However, the uses of internet have created new set of challenges. Adolescents have been identified as a vulnerable group to be affected. But Internet is a reality that we just cannot ignore; neither can we ignore the effects of its excessive use. So, it was necessary to identify the effects of problematic internet use among the adolescents which the researchers tried to do. This was a cross sectional study, conducted from May 2019 to September 2020 in a renowned school in Dhaka where 305 students of 13 to 17 years of either sex were included conveniently. A questionnaire containing socio-demographic variables, internet addiction test (IAT) and strengths and difficulties questionnaires were applied. The result showed that, 37.7% of the participants were problematic internet users. Behaviors such as emotional, conduct, hyperactivity, peer problems and pro social were significantly associated (p<0.0001) with problematic internet use. Problematic internet users (PIU) also had a great deal of difficulties that upset those, a great interfere with home life, friendship, class room learning and leisure activities. Research findings suggest that school going adolescents are in risk of psychiatric disorders due to problematic internet use and often kept undetected. So, researchers recommend country wide screening program to address this issue. Bang J Psychiatry 2021;35(2): 23-27